2009
DOI: 10.1080/08860220902839089
|View full text |Cite
|
Sign up to set email alerts
|

Is Serum Cystatin C an Accurate Endogenous Marker of Glomerular Filteration Rate for Detection of Early Renal Impairment in Patients with Type 2 Diabetes Mellitus?

Abstract: Background. Researches have recently reported that serum cystatin C is a more sensitive marker of changes in glomerular filtration rate (GFR) than serum creatinine. We conducted this study to evaluate the significance of serum cystatin C as a more sensitive marker of GFR for early detection of renal impairment in special groups of patients with type 2 diabetes mellitus (DM).Methods. The present study included 40 patients with type 2 DM divided into four equal groups based on their urinary albumin excretion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
1
12
0
3
Order By: Relevance
“…Subsequently, full‐text articles of the remaining 53 records were assessed and 36 were further excluded due to inability to reconstruct 2 × 2 tables. As a result, 17 studies were included in this analysis [Fig. ].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, full‐text articles of the remaining 53 records were assessed and 36 were further excluded due to inability to reconstruct 2 × 2 tables. As a result, 17 studies were included in this analysis [Fig. ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Hojs et al [3], Kyhse-Andersen et al [19], El-Shafey et al [20], Xu et al [21], Thomas and Thomas [4], Yashiro et al [6], Mojiminiyi and Abdella [22], Maillard et al [23], and Qutb et al [8] all found that the diagnostic accuracy of CyC for reduced GFR was superior to that of sCr based on ROC curves. El-Shafey et al [20] reported that CyC was more sensitive than Cr for detecting early and moderate deterioration of GFR in adult renal transplant recipients and in patients with type 2 diabetes mellitus and renal impairment. A meta-analysis of 24 studies examining the clinical utility of CyC revealed that CyC was superior to sCr for detecting impaired GFR [5].…”
Section: Discussionmentioning
confidence: 99%
“…Na prikazu ROC krive je oblast koju pokriva CKD-EPI iznosila 0,973, za MDRD 0,887, a za klirens kreatinina 0,819. El-Shafey i saradnici [19] su pokazali da je oblast koju pokriva ROC kriva bila najviša za jednačinu JGF iz cistatina C u odnosu na jednačinu iz kreatinina i 24-časovni kreatinin. Slične rezultate pokazao je MacIsaac sa saradnicima [20].…”
Section: Diskusijaunclassified